Antagonism of antifungal metabolites from Streptomyces griseus H7602 against Phytophthora capsici. (19th February 2014) - Nguyen, Xuan Hoa; Naing, Kyaw Wai; Lee, Young Seong; Kim, Yong Hwan; Moon, Jae Hak; Kim, Kil Yong
<x xml:space="preserve">Abstract</x> In this study, evidences for antagonism were established by production of antifungal metabolites from Streptomyces griseus H7602, which were active to inhibit mycelial growth of Phytophthora capsici in the in vitro assays. Mycelial growth and zoosporangia formation of P. capsici was strongly inhibited in the medium containing the cell free culture filtrate of S. griseus H7602. Antifungal metabolites from the cell free culture filtrate of S. griseus H7602 showed substantial antagonistic effects on P. capsici. In addition, a purified antifungal compound was separated from the antifungal metabolites of S. griseus H7602 and identified to be 1H‐pyrrole‐2‐carboxylic acid (PCA) by spectra analyses. PCA showed strong antifungal activity and was evaluated for the first time for its antagonism against P. capsici under in vitro conditions. Minimum inhibitory concentration (MIC) value of PCA was low (4 µg ml−1), and the mycelial growth of P. capsici was almost inhibited at concentration of 64 µg ml−1. This study suggests that the PCA may be useful as biofungicides against P. capsici, and the prominent antagonism of antifungal metabolites from S. griseus H7602 highlights it as a candidate for biocontrol of P. capsici.